2022
DOI: 10.3390/su14116498
|View full text |Cite
|
Sign up to set email alerts
|

Food Environment Inequalities and Moderating Effects of Obesity on Their Relationships with COVID-19 in Chicago

Abstract: The COVID-19 outbreak has raised challenges for people with health problems. Obesity is a global issue related to COVID-19. The Centers for Disease Control (CDC) finds that obesity worsens COVID-19 outcomes. As body mass index increases, the COVID-19 death risk increases. Additionally, due to different restriction policies, the pandemic has transformed our food environment. Thus, it is important to develop an antivirus-enabled paradigm to decrease the COVID-19 spreading rate in neighborhoods with obesity conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…This finding along with consistent results observed in previous studies suggest that long-term food insecurity may impact COVID-19 outcomes. 5 , 47 , 48 In addition, we also found that higher long-term access to fitness and recreational sports centers is associated with lower odds of COVID-19 hospitalization. While no previous study has examined access to fitness centers and COVID-19 outcomes, the results observed in this study are consistent with the well-established protective associations between physical activity and COVID-19 outcomes.…”
Section: Discussionsupporting
confidence: 54%
“…This finding along with consistent results observed in previous studies suggest that long-term food insecurity may impact COVID-19 outcomes. 5 , 47 , 48 In addition, we also found that higher long-term access to fitness and recreational sports centers is associated with lower odds of COVID-19 hospitalization. While no previous study has examined access to fitness centers and COVID-19 outcomes, the results observed in this study are consistent with the well-established protective associations between physical activity and COVID-19 outcomes.…”
Section: Discussionsupporting
confidence: 54%
“…The tract-level estimates, which are assessed in several prior studies [85,86], have certain limitations. The outcome variable was collected by means of a telephone survey which likely faces problems due to recall bias and social desirability bias [87,88].…”
Section: Limitationsmentioning
confidence: 99%
“…Obesogenic environments are characterised by easy access to fast food restaurants both offline and online (Gordon-Larsen, 2014;Horta et al, 2022;Miles et al, 2022;Paulitsch & Dumith, 2021;Pechey & Marteau, 2018), in which most of the foods offered are high calorie. This situation may have an unwitting effect on their health (Dreher et al, 2019;Huang, 2022), the long-term consequences of consuming high-calorie foods can lead to overweight and obesity, as suggested by several studies (Beslay et al, 2020;Elliston et al, 2017;Gordon-Larsen, 2014;Navarro & Vélez, 2019;Paulitsch & Dumith, 2021;Rahman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%